Force Generation and Muscle Activation: A Literature Review of Lower Limb Mechanics in Softball Batting - Muhammad Fahrezi Harahap; Zukhro Bahadirovna Khamraeva; Gorgan Carmina Mihaela (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. In order to conduct a thorough examination of the biomechanical principles underlying lower limb functionality during softball batting, this study aims to specifically elucidate the contributions of ground reaction forces, patterns of muscle activation, and the temporal sequencing of these factors in influencing overall batting performance. Materials and methods. A systematic review was conducted following PRISMA guidelines, searching electronic databases for peer-reviewed research from January 2000 to December 2024. The study initially identified 156 potentially relevant articles, with 24 studies ultimately meeting the stringent inclusion criteria. Researchers utilized advanced measurement techniques including surface electromyography, motion capture systems, and force plate analysis to examine lower limb biomechanics. Results. Elite softball players demonstrated significantly more precise lower limb mechanics compared to intermediate players. Key findings include peak rear leg ground reaction forces ranging from 1.6 to 1.8 times body weight, compared to 1.2 to 1.4 times for intermediate players. Muscle activation showed a sequential pattern progressing from gluteal muscles through quadriceps to gastrocnemius, with a strong correlation to bat speed (r=0.72, p<0.01). Temporal sequencing was crucial, with elite players exhibiting a coefficient of variation of 8.3% compared to 15.7% for intermediate players. Conclusions. The study reveals that successful softball batting depends not on raw strength, but on the sophisticated coordination of lower limb biomechanics. Precise timing, muscle recruitment patterns, and efficient energy transfer through the kinetic chain are critical for optimal batting performance. The research provides evidence-based recommendations for targeted training interventions that focus on movement coordination and biomechanical efficiency.